FUNCTIONAL PERSPECTIVE IN THE NAHWU LEARNING - Wildan Nur Haifani; Azizah Arum Muslihatin (RETEL Journal (Journal on Publication of The Research on Teaching and Language), 2020)
This study iscusses functional nahwu, which in general is a characteristic of nahwu that seeks to present Nahwu's rules in an easy, simple method, and away from boring long-winded and overly concise discussions. The method used in this research is library research or library study by gathering literature and writing related to functional nahwu. In some books, found functional aspects which have advantages and disadvantages in the contents of each book.The four books dissected in this paper have a cursory functional characteristics as mentioned in the discussion above. However, after awareness, it is clear that among the four have different considerations in applying the functional aspects. Keyword: Functional, Nahwu, Learning, Perspective